KEBIJAKAN SISTEM PEMIDANAAN DALAM UPAYA PENANGGULANGAN PENYALAHGUNAAN SENJATA API YANG DILAKUKAN OLEH ANGGOTA TENTARA NASIONAL INDONESIA - Fajar Margiyati Awaludin, Eko Soponyono , Purwoto (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Legal policy is one factor that take an important role in the context of state law. Policies in making a good criminal law essentially inseparable from crime prevention efforts. The sentencing system is part of the efforts to combat crime through penal using criminal law policy. According to data obtained from the Military Court of Yogyakarta, one of the crimes committed by members of the Indonesian military (TNI) is the misuse of firearms.